2011
DOI: 10.1073/pnas.1104666108
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates of cognitive capacity limitations

Abstract: Cognition has a severely limited capacity: Adult humans can retain only about four items "in mind". This limitation is fundamental to human brain function: Individual capacity is highly correlated with intelligence measures and capacity is reduced in neuropsychiatric diseases. Although human capacity limitations are well studied, their mechanisms have not been investigated at the single-neuron level. Simultaneous recordings from monkey parietal and frontal cortex revealed that visual capacity limitations occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

52
309
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(365 citation statements)
references
References 43 publications
52
309
1
3
Order By: Relevance
“…Here, we propose that the precision of the neural coding of information in short-term memory contributes to variations in memory capacity. This view is consistent with electrophysiological recordings in monkeys showing that visual capacity limitations appear immediately upon stimulus encoding, in a bottom-up manner (Buschman, Siegel, Roy, & Miller, 2011). Accordingly, our behavioral data suggest that human subjects' memory for individual locations is accurate but imprecise.…”
Section: Memory Capacitysupporting
confidence: 77%
“…Here, we propose that the precision of the neural coding of information in short-term memory contributes to variations in memory capacity. This view is consistent with electrophysiological recordings in monkeys showing that visual capacity limitations appear immediately upon stimulus encoding, in a bottom-up manner (Buschman, Siegel, Roy, & Miller, 2011). Accordingly, our behavioral data suggest that human subjects' memory for individual locations is accurate but imprecise.…”
Section: Memory Capacitysupporting
confidence: 77%
“…A similar quantity limitation has also been revealed in monkey neurophysiological studies [46,47] . In addition, studies have shown that neurons in the PFC of numerically naive monkeys tune to a preferred numerosity [48] , independent of sensory modality [49] .…”
Section: Prefrontal Cortex and Wm Quantitysupporting
confidence: 69%
“…Charron and Koechlin have proposed that the frontal lobes in the two hemispheres represent two concurrent goals [50] . Similar hemispheric limitation has also been proposed through neurophysiological data from non-human primates [47] . Further, the frontal lobe in each hemisphere can be subdivided according to the abstraction Neurosci Bull April 1, 2015, 31(2): 175-182 178 of processed goals, which may result in different capacity limits for each hierarchy [51] .…”
supporting
confidence: 55%
See 1 more Smart Citation
“…The proposal here is that the hippocampus has a gearing mechanism, except the number of gears is as high as the number of phase timings which can integrate and decouple. Such a number has been defined for STM as correlated to the theta -gamma interaction intitally as 7 +/-2 ( Jensen and Lisman, 1996a) and more latterly as 2 items per hemisphere (Buschman et al, 2011). To bolster the gearing concept as present in critical transition areas between the cortex and limbic system, hippocampal place cells are also proposed as speed-controlled oscillators (Geisler et al, 2007).…”
Section: A "Gearing" Model For the Information Engine ?mentioning
confidence: 99%